Soil liquefaction in the Tone river basin during the 2011 earthquake off the Pacific coast of Tohoku - Lenart, Stanislav (Acta geotechnica Slovenica, 2012)
A brief report about the liquefaction damage in the Tone river basin, caused by the 2011 earthquake off the Pacific coast of Tohoku, is presented. It includes sand boiling, damage to river dikes, the settlement and tilt of superstructures, the uplift of light underground structures and lateral spreading. A history of land reclamation along the Tone river is briefly presented to understand why extensive liquefaction took place predominantly inreclaimed land. The recorded ground motions near the river were analyzed andcompared to near-source ground motions. The effects of the site location and the ground conditions during the peak ground acceleration are discussed.
Keywords: 2011; geotehnika; Japonska; potresi; utekočinjanje tal